Facilitation cascades create a predation refuge for biodiversity in a novel connected habitat - Brendan S. Lanham; Alistair G. B. Poore; Paul E. Gribben (Ecosphere, 2020)
Abstract Communities structured via facilitation cascades whereby one habitat‐forming species promotes a secondary habitat‐forming species with synergistic effects on biodiversity are increasingly documented. Habitat‐formers can also extend the realized niche of other habitat‐forming species by facilitating their recruitment into novel environments across heterogeneous landscapes. However, further understanding of whether secondary habitat‐formers in these novel environments differ in their structure or support different communities from those settled in their natal habitat is required. Here, we investigated whether abiotic and biotic conditions in a novel connected habitat influence biodiversity within a secondary habitat‐former facilitated outside its natal habitat. We contrasted the morphology of the habitat‐forming alga, Sirophysalis trinodis, and its associated fish and epifaunal community occurring on rocky reef (natal habitat) and on nearby a biogenic hard substrate, live clam shells (novel habitat) in soft sediments. The algae on clams had a different morphology to those on the rocky shore and supported increased abundance of some epifaunal species. A reciprocal transplant experiment of S. trinodis individuals among habitats found that differences in the abundance of epifauna were explained by the increased abundance and consumption rates of predatory fish on the reef habitat compared to soft‐sediment habitats, and not by differences in algal morphology between habitats. We demonstrate that facilitation promotes a secondary habitat‐former into a novel habitat, which then enhances the abundance of associated epifauna by providing a predation refuge. This study contributes to a small but growing body of research demonstrating landscape‐scale effects of facilitation cascades, and that basal habitat‐formers can extend the realized niche of secondary habitat‐formers and their associated communities.